Cosmopolitan Attitudes and Cosmopolitan Identities in Amitav Ghosh's The Shadow Lines. Issue 3 (2nd October 2022) - Jackson, Elizabeth
Abstract: Distinguishing between cosmopolitan attitudes and cosmopolitan identities, I argue that although the idea of "cosmopolitanism" has recently been endorsed as an ethical attitude by many writers, readers, and scholars from a range of disciplines, there has been a surprising amount of hostility toward individual people with complex cosmopolitan identities. Amitav Ghosh's novel The Shadow Lines vividly illustrates this divergence by dramatizing the ways in which the nation is indeed an "imagined community, " while at the same time portraying the plight of a character who is continually subjected to various forms of exclusion, Othering, and even disapproval because of her global upbringing which generates her cosmopolitan identity.